2022
DOI: 10.1002/ddr.21961
|View full text |Cite
|
Sign up to set email alerts
|

Papaverine, a promising therapeutic agent for the treatment of COVID‐19 patients with underlying cardiovascular diseases (CVDs)

Abstract: The causative agent of coronavirus disease‐2019 (COVID‐19), severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), enters the host cells via an angiotensin‐converting enzyme 2 (ACE2)‐mediated endocytosis‐dependent manner. Because ACE2 is highly expressed in the heart, SARS‐CoV‐2 can severely infect heart tissue and arteries, causing acute and chronic damage to the cardiovascular system. Therefore, special attention should be paid to finding appropriate agents to protect this vital system during COVID‐19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Menadione, cephaeline, cycloheximide, and pyrvinium identified in this study may be potential therapeutic agents for COVID-19. Several investigations had confirmed the efficacy of the above drugs for the treatment of COVID-19 [120,121].…”
Section: Discussionmentioning
confidence: 89%
“…Menadione, cephaeline, cycloheximide, and pyrvinium identified in this study may be potential therapeutic agents for COVID-19. Several investigations had confirmed the efficacy of the above drugs for the treatment of COVID-19 [120,121].…”
Section: Discussionmentioning
confidence: 89%
“…In continuation of our recent efforts to find suitable therapeutic agents to combat COVID‐19 disease (Valipour, 2022a; Valipour, 2022b; Valipour, 2022c; Valipour et al, 2021; Valipour et al, 2022a; Valipour et al, 2022b), in this study, we review the therapeutic potential of a wide range of isoquinoline alkaloids for the treatment of this disease (Figure 2). As will be explained below, isoquinoline alkaloids that simultaneously have antiviral effects and modulatory activity against the p38 MAPK signaling pathway have a higher therapeutic chance for this purpose.…”
Section: Isoquinoline Alkaloids With a High Potential To Inhibit Sars...mentioning
confidence: 99%
“…Data propose that 6 exhibits its inhibitory activity at the terminal stage of the viral life cycle [ 229 , 230 ]. Recent studies revealed that 6 suppresses the cytopathogenic effects of SARS-CoV-2 (EC 50 = 1.1 μM) [ 231 ].…”
Section: Kinases Inhibitors In Various Developmental Stages As Antivi...mentioning
confidence: 99%